PENGARUH TERAPI SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) TERHADAP PERUBAHAN NILAI ANKLE BRACHIALE INDEX (ABI) PADA PASIEN DIABETES MELITUS TIPE 2 - pitoyo, joko (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2019)
Abstract: Patients with type 2 diabetes mellitus the risk of developing peripheral artery disease because blood circulation is disrupted. The way to detect peripheral arterial disease early can be through the ABI examination by comparing the systolic blood pressure in the ankle with systolic blood pressure in the brachialis. Patients with diabetes mellitus are often found to have high systolic blood pressure checks. One way to reduce blood pressure in patients with diabetes mellitus is relaxation, namely the therapy SEFT. The research design used was quasy experimental with time series design. The sample was 30 people using purposive sampling technique according to inclusion criteria. The research instrument used is the observation sheet. Methods of data analysis using the Paired T-Test. The results showed that before the treatment of almost all the values ​​of the ABI showed the presence of moderate arterial disease and after treatment most showed acceptable. Based on Paired T-Test significant value 0.000 which means there is influence therapeutic SEFT to changes in ABI value in patients with type 2 diabetes mellitus so this relaxation technique can be used as a complementary therapy for patients with diabetes mellitus who are at risk of peripheral arterial disease.